2005
DOI: 10.1099/vir.0.80907-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of classical swine fever virus protein E2 as a target for cytotoxic T cells by using mRNA-transfected antigen-presenting cells

Abstract: Vaccination of pigs against Classical swine fever virus (CSFV) by using live-virus vaccines induces early protection before detectable humoral immune responses. Immunological analyses indicate that this is associated with T-cell activation, underlining the importance of targeting cytotoxic T-lymphocyte (CTL) responses for vaccine improvement. Antigen-presenting cells (APCs) transfected with mRNA encoding structural protein E2 or non-structural viral proteins NS3-NS4A were used to identify viral genes encoding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 43 publications
3
28
0
Order By: Relevance
“…Subsequently, mature and activated DC subsets would then be involved in induction of adaptive immune responses, illustrated by punctual IFN-γ and IL-18 secretions in serum. This was in agreement with CTL stimulation by CSFV-infected mature mo-DC [14] and with the initiation of cellular immune responses described in pigs surviving infection [35]. Additionally, the fact that high proportions of both DC subsets expressed IL-10 in the spleen could reflect the starting of humoral immune response, in accordance with the detection of secreting IgM E2 + B cells the first days post-infection [39].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Subsequently, mature and activated DC subsets would then be involved in induction of adaptive immune responses, illustrated by punctual IFN-γ and IL-18 secretions in serum. This was in agreement with CTL stimulation by CSFV-infected mature mo-DC [14] and with the initiation of cellular immune responses described in pigs surviving infection [35]. Additionally, the fact that high proportions of both DC subsets expressed IL-10 in the spleen could reflect the starting of humoral immune response, in accordance with the detection of secreting IgM E2 + B cells the first days post-infection [39].…”
Section: Discussionsupporting
confidence: 88%
“…It was shown that CSFV replicates in mo-DC without cytopathological effect but prevents their activation and thereby the secretion of IFN-α, tumor necrosis factor (TNF)-α, interleukin (IL)-6, IL-10 and IL-12 [4,13]. CSFV also blocks mo-DC maturation by inhibiting MHC-II up-regulation, although these cells remain able to present E2 viral envelop glycoprotein to cytotoxic T lymphocytes [14]. Similarly, CSFV replicates in NIPC [4].…”
Section: Introductionmentioning
confidence: 99%
“…CD107a is expressed on the cell surface following activation-induced degranulation, and it has been described as a marker for cytotoxic CD8 T cell activity whose expression has been associated with loss of perforin following antigen stimulation (34). The data presented here suggest that CSFV-specific IFN-␥-expressing cells may also have cytotoxic capacity and consolidate our previous results where we showed that IFN-␥ expression was restricted to CD8 T cells expressing intracellular perforin (7) and other earlier studies that demonstrated CSFV-specific cytotoxic activity by T cell cultures isolated from vaccinated pigs (8)(9)(10). While IFN-␥-secreting T EM cells have been implicated in protection against a variety of intracellular pathogens, simultaneous production of IFN-␥, TNF-␣, and IL-2 detected at the single-cell level by multiparameter flow cytometry has been correlated with enhanced vaccine-induced protection (45)(46)(47)(48)(49)(50)(51).…”
Section: Discussionsupporting
confidence: 78%
“…Moreover, it has recently been shown that there is a close temporal correlation between the induction of CSFV-specific T cell IFN-␥ responses and rapid protection induced by a C-strain vaccine (6). In addition to the secretion of IFN-␥, which has been shown to exert direct antiviral effects on CSFV in vitro (7), vaccine-induced CSFV-specific T cells have also been shown to have the capacity to lyse infected cells with specificities mapped to the structural protein E2 and the nonstructural protein NS3 (8)(9)(10). Flow cytometric studies have identified both CD4 and CD8 T cells as the cellular source of CSFV-specific IFN-␥, with the latter coexpressing the cytolytic molecule perforin (7,11).…”
mentioning
confidence: 99%
“…CTL assays. A standard chromium ( 51 Cr) release assay was used to measure antigen-specific T cell cytotoxicity as previously described (37).…”
Section: Methodsmentioning
confidence: 99%